PENGELOLAAN ARMADA KENDARAAN MELALUI APLIKASI FLEET MANAGEMENT SYSTEM - Kiki Kusumawati; Dimas Rizky Prastyo; Malika Zyahira Fajri; Amanda Hafinah; Yehezklie Maro (FAKULTAS TEKNIK, 2024)
The development of information technology grows and develops so rapidly every year. Likewise in the current digital era which has begun to complement each other between information and communication technology, where both are integrated to produce a renewable innovation output. With the integration of information and communication technology, it is able to have a positive impact on the world of the transportation industry, especially in terms of managing the vehicle fleet as a means of transportation that also needs to get good attention and care so that the vehicle fleet to support business and business activities is in prime condition and is environmentally friendly. The purpose of this vehicle fleet management application is to monitor the condition of the vehicle fleet in prime condition when it will be operated to support business and business activities. The output of this application is a fleet management system application that has the ability to store and manage vehicle fleet data that can function to monitor the condition of the vehicle fleet, and the deadline for monitoring vehicle tax payments.